Maternal Long-Chain Polyunsaturated Fatty Acid Status, Methylmercury Exposure, and Birth Outcomes in a High-Fish-Eating Mother–Child Cohort. Issue 7 (20th May 2020) - Yeates, Alison Jayne; Zavez, Alexis; Thurston, Sally W; McSorley, Emeir M; Mulhern, Maria S; Alhamdow, Ayman; Engström, Karin; Wahlberg, Karin; Strain, J J; Watson, Gene E; Myers, Gary J; Davidson, Philip W; et al.
ABSTRACT: Background: Maternal status of long-chain PUFAs (LC-PUFAs) may be related to fetal growth. Maternal fish consumption exposes the mother to the neurotoxicant methylmercury (MeHg), which, in contrast, may restrict fetal growth. Objective: Our aim was to examine relations between maternal LC-PUFA status at 28 wk and birth outcomes (birth weight, length, and head circumference), controlling for MeHg exposure throughout pregnancy, in the Seychelles Child Development Study Nutrition Cohort 2. Our secondary aim was to examine the influence of maternal variation in genes regulating the desaturation of LC-PUFAs [fatty acid desaturase (FADS)] on birth outcomes. Methods: From nonfasting blood samples collected at 28 wk of gestation, we measured serum total LC-PUFA concentrations and FADS1 (rs174537, rs174561), FADS1–FADS2 rs3834458, and FADS2 rs174575 genotypes, with hair total mercury concentrations assessed at delivery. Data were available for n = 1236 mother–child pairs. Associations of maternal LC-PUFAs, MeHg, and FADS genotype with birth outcomes were assessed by multiple linear regression models, adjusting for child sex, gestational age, maternal age, BMI, alcohol use, socioeconomic status, and parity. Results: In our cohort of healthy mothers, neither maternal LC-PUFA status nor MeHg exposure were significant determinants of birth outcomes. However, when compared with major allele homozygotes, mothers who were heterozygous for the minor allele of FADS1 (rs174537 and rs174561, GT compared with TT, β = 0.205, P = 0.03; TC compared with CC, β = 0.203, P = 0.04) and FADS1–FADS2 (rs3834458, Tdel compared with DelDel, β = 0.197, P = 0.04) had infants with a greater head circumference (all P < 0.05). Homozygosity for the minor allele of FADS2 (rs174575) was associated with a greater birth weight (GG compared with CC, β = 0.109, P = 0.04). Conclusions: In our mother–child cohort, neither maternal LC-PUFA status nor MeHg exposure was associated with birth outcomes. The observed associations of variation in maternal FADS genotype with birth outcomes should be confirmed in other populations.